Elemental Diet Accelerates the Recovery From Oral Mucositis and Dermatitis Induced by 5-Fluorouracil Through the Induction of Fibroblast Growth Factor 2 - Koji Harada PhD, DDS; Tarannum Ferdous PhD; Hiroaki Kobayashi MD; Yoshiya Ueyama PhD, DDS (Integrative Cancer Therapies, 2018)
Mucositis and dermatitis induced by anticancer agents are common complications of anticancer therapies. In this study, we evaluated the efficacy of Elental (Ajinomoto Pharmaceutical Ltd, Tokyo, Japan), an elemental diet with glutamine in the treatment of 5-fluorouracil (5-FU)-induced oral mucositis and dermatitis in vivo and tried to clarify the underlying mechanisms of its action. Oral mucositis and dermatitis was induced through a combination of 5-FU treatment and mild abrasion of the cheek pouch in hamsters and the dorsal skin in nude mice respectively. These animals received saline, dextrin or Elental suspension (18 kcal/100 g) by a gastric tube daily until sacrifice. Elental reduced oral mucositis and dermatitis more effectively than dextrin in the animal model. Moreover, growth facilitating effects of Elental on HaCaT cells were examined in vitro. MTT assay, wound healing assay, and migration assay revealed that Elental could enhance the growth, invasion, and migration ability of HaCaT. ELISA and Western blotting showed upregulated FGF2 in Elental-treated HaCaT. These findings suggest that Elental is effective for the treatment of mucositis and dermatitis, and may accelerate mucosal and skin recovery through FGF2 induction and reepithelization.